The Translation of Cultural Terms in The Balinese Folktales - Dewi Rupini, Luh Nitya; Sedeng, I Nyoman; Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This study is entitled “The Translation of Cultural Terms in The Balinese Folktales ”. This study is aimed at to identify the categories of cultural words and describe about translation procedure. The data were taken directly from Balinese Folktales in internet . Documentation method was used as the method in collecting data; finding the cultural words, note taking and classifying. In analyzing the data, qualitative method was applied. In presenting the analysis, this study used descriptive method. The main theory was proposed by Newmark (1988:95). There was also the other theory by Newmark (1988:45) as the theory of translation procedures. The results of this study showed that the most used types of cultural words found in this study were ecology, material culture and social culture. In connection with translation procedure, there were only three types of translation procedure found in Balinese folktales. The translation procedures used were Literal translation, cultural equivalent, and descriptive equivalent. By translating books from Balinese to English can make other people who read and learn about Balinese culture understand easily. Also, it is the media to introduce Balinese culture to the world.